Karakteristik Pasteurella multocida Penyebab Pasteurellosis pada Babi di Kota Kupang Provinsi Nusa Tengggara Timur - Victor Lenda; Filphin A. Amalo; Yulfia N. Selan (JURNAL KAJIAN VETERINER, 2019)
The number of commercial pigs in East Nusa Tenggara has grown fast with a population of 1,739,481, and has become more potential. However, the mixed farming model has become one of the factor of potentially high in the transmission of disease-causing pathogenic microorganisms. One of the microorganism is Pasteurella multocida which causes pasteurellosis, has been identified in 25% of slaughtered pigs (Maes et al., 2001). One of the clinical symptom due to pasteurellosis in pigs is the occurrence of bronchopneumonia in pulmo and inflammation in various visceral organs, such as the heart and kidneys. the phenotypic characteristization of this bacteria, will be very helpful in designing a comprehensive prevention and treatment programs of pig pasteurellosis. The aim of the research was to determine the characteristics of P. multocida related to pasteurellosis and recording of the disease in Kupang, NTT. This research also find out the phenotipyc characteristics of P. multocida species from pigs and the possibility of transmission among sensitive species. A total of 30 swine lung samples of pulmo were obtained from slaughterhouse in Kupang to carry out this study. Pulmo taken from slaughtered pigs that showed clinical respiratoric symptoms such as dyspnoea and the presence of serous to mucopurulent nasal exudates, and the specific lesions of gray hepatization in pulmo. The collected samples were then processed for histopathological and microbiological studies. Out of the total 30 sample, 15 samples were found to be suspected for pasteurellosis, and 3 samples were successfully confirmed to be positive for Pasteurella multocida. Varied macroscopic changes showed pathognomonic lesions as multifocal hemorrhage and congestion of the pulmonary lobes. Serous to mucopurulent exudate were found in lumen bronchus. Multi lobes grayed hepatization and multifocal hemorrhage were observed in the pulmo. Histopatologic analysis showed three types of pneumonia that were multifocal suppurative bronchopneumonia with neutrophil infiltration into alveoli and bronchioles; non-suppurative pneumonia as fibrinous bronchopneumonia with severe congestion, and chronic bronchiolitis with infiltration of mononuclear cell and thickening of fibrous tissue on bronchioles. Bacterial culture from the samples showed circular, convex and non hemolytic colony on blood agar base. Gram staining’s showed Gram negative microorganism with coccoid bipolar structure, which are some of the characteristic of the microorganism.. It was concluded that the samples is having P. multocida infection. Although, some isolate on MacConkey showed lactose fermentation and tolerance to bile salts that were not the nature of the microorganism, isolation and identification from other organs needed to be done, for example from the heart and kidneys, are needed.